Equilibrium Labor Market Search and Health Insurance Reform - Aizawa, Naoki; Fang, Hanming (Journal of Political Economy, 2020)
We present and empirically implement an equilibrium labor market search model where risk-averse workers facing medical expenditure shocks are matched with firms making health insurance coverage decisions. We use our estimated model to evaluate the equilibrium impact of many health care reform proposals, including the 2010 Affordable Care Act (ACA). We use the estimates of the early impact of the ACA as a model validation. We find that income-based subsidies for health insurance premiums are crucial for the sustainability of the ACA, while the ACA can still substantially reduce the uninsured rate without the individual or the employer mandate.